Literacy Strategies in Mathematics Learning: A Reflective Review in Teacher Education - Maharani, Anggita; Nazilah, Amy Siti; Laelasari; Hartono, Wahyu (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aims to explore the experiences of Teacher Professional Education [TPE] students in applying literacy strategies in mathematics learning and evaluate their impact on students' understanding of mathematics concepts and literacy skills. Using a qualitative approach, this study involved TPE students of the Mathematics Education Study Program at Universitas Swadaya Gunung Jati Cirebon in batch 1 of 2023, selected through a purposive sampling technique. Data were collected through interviews and subsequently analyzed qualitatively, following systematic steps that included thematic mapping, pattern searching, category identification, and meaning interpretation. The findings show that the implementation of literacy strategies, such as visualization, discussion, and reading of mathematical texts, positively impacts students' understanding and engagement in mathematics learning. Challenges encountered while integrating literacy strategies include time constraints and the selection of relevant materials. However, a strong desire to learn and a commitment to constant evaluation helped to overcome these obstacles.. To promote future literacy strategies in mathematics education, actions such as teacher training, technology integration, curriculum adjustment, and appropriate reading materials are required.